Angiotensin-converting enzyme inhibitors and angiotensin II receptor blockers: potential allies in the COVID-19 pandemic instead of a threat?. Issue 8 (30th April 2021) - Simko, Fedor; Baka, Tomas
Abstract: Angiotensin-converting enzyme 2 (ACE2) is the leading player of the protective renin–angiotensin system (RAS) pathway but also the entry receptor for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). RAS inhibitors seemed to interfere with the ACE2 receptor, and their safety was addressed in COVID-19 patients. Pedrosa et al. ( Clin. Sci. ( Lond. ) (2021), 135, 465–481) showed in rats that captopril and candesartan up-regulated ACE2 expression and the protective RAS pathway in lung tissue. In culture of pneumocytes, the captopril/candesartan-induced ACE2 up-regulation was associated with inhibition of ADAM17 activity, counterbalancing increased ACE2 expression, which was associated with reduced SARS-CoV-2 spike protein entry. If confirmed in humans, these results could become the pathophysiological background for justifying RAS inhibitors as cornerstone cardiovascular protectives even during COVID-19 pandemic.